CHARACTERISTICS OF ORGANIC AND NUTRIEN REMOVAL ON LOOP BIOFILTER SYSTEM FOR PEAT WATER AND WASTEWATER TREATMENT - Elis Hastuti; Fitrijani Anggraini; Reni Nuraeni (Pusbindiklat - LIPI, 2017)
Domestic wastewater pollution in the watershed area which has ecologically sensitive area, such as peat water, can be resolved by water management that combines raw water treatment and wastewater treatment with closed loop system on a community scale. This paper describes the removal characteristics of organic and nutrient in biofilters loop system to treat raw water that contains color <300 units PtCo, COD 102-116 mg/L, and domestic wastewater. Water treatment system which consists of a biological treatment and multimedia filtration is used to supply drinking water and to conduct wastewater treatment on a community scale by using the potential of ecosystems and chemical-physical characteristics of peat. The study was conducted by applying method of field scale to serve 50 families and method of performance evaluation models based on approach of first-order kinetics plug flow and Kadlec and Knight k-C* model. The case study is located in downstream of Siak watershed areas, as one of the national strategic watersheds, which is packed with urban slum areas with low access to surface water utilization and good sanitation infrastructure. Water treatment unit that consists of peat biofilter systems, hybrid aerobic biofilter, and zeolite cation-anion filtrationcan support water supply in public sanitation facilities. The biofilters loop model for wastewater treatment consists of hybrid Upflow Anaerobic Sludge Blanket (UASB), biofilters, and constructed wetlands which its media is a combination between porous media and peat soils. At steady state, the removal of organic and nitrogen is larger than 90%.